Morphological and mechanical properties of muscle and tendon in highly trained sprinters - Kubo, K.; Ikebukuro, T.; Yata, H.; Tomita, M.; Okada, M. (Journal of Applied Biomechanics, 2011)
The purpose of this study was to investigate muscle and tendon properties in highly trained sprinters and their relations to running performance. Fifteen sprinters and 15 untrained subjects participated in this study. Muscle thickness and tendon stiffness of knee extensors and plantar flexors were measured. Sprinter muscle thickness was significantly greater than that of the untrained subjects for plantar flexors, but not for knee extensors (except for the medial side). Sprinter tendon stiffness was significantly lower than that of the untrained subjects for knee extensors, but not for plantar flexors. The best official record of a 100-m race was significantly correlated to the muscle thickness of the medial side for knee extensors. In conclusion, the tendon structures of highly trained sprinters are more compliant than those of untrained subjects for knee extensors, but not for plantar flexors. Furthermore, a thicker medial side of knee extensors was associated with greater sprinting performance.